2012
DOI: 10.1016/j.theriogenology.2012.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two estradiol esters (benzoate and cypionate) on the induction of synchronized ovulations in Bos indicus cows submitted to a timed artificial insemination protocol

Abstract: The effects of estradiol benzoate (EB) and estradiol cypionate (EC) on induction of ovulation after a synchronized LH surge and on fertility of Bos indicus females submitted to timed AI (TAI) were evaluated. In Experiment 1, ovariectomized Nelore heifers were used to evaluate the effect of EB (n = 5) and EC (n = 5) on the circulating LH profile. The LH surge timing (19.6 and 50.5 h; P = 0.001), magnitude (20.5 and 9.4 ng/mL; P = 0.005), duration (8.6 and 16.5 h; P = 0.001), and area under the LH curve (158.6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
2
26

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(93 citation statements)
references
References 23 publications
7
46
2
26
Order By: Relevance
“…Estradiol (E2)-and progesterone (P4)-based estrus synchronization protocols have been successfully used to control follicular and luteal dynamics in cattle and to synchronize ovulation when inseminating without estrus detection (Baruselli et al, 2004, Bó et al, 2002, Sá Filho et al, 2010band Sales et al, 2012. Common among these protocols is the insertion of an intravaginal P4 device or a progestin ear implant, plus the administration of an E2 ester on Day 0 [estradiol benzoate (EB) or estradiol valerate to induce the emergence of a new follicular wave], prostaglandin (PG) F 2α on the day of device withdrawal (to ensure luteolysis) and an ovulation inducer used at implant removal, 24 h later or concurrent with the TAI to induce synchronized ovulation (Baruselli et al, 2004, Sá Filho et al, 2011aand Sales et al, 2012.The treatment of cattle with equine chorionic gonadotropin (eCG) has been suggested as an effective tool to increase follicular development and pregnancy per AI (P/AI) in suckled beef cows that exhibit a high prevalence of anestrus or a low body condition score (Baruselli et al, 2004, Sá Filho et al, 2010a, Sá Filho et al, 2010cand Sales et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estradiol (E2)-and progesterone (P4)-based estrus synchronization protocols have been successfully used to control follicular and luteal dynamics in cattle and to synchronize ovulation when inseminating without estrus detection (Baruselli et al, 2004, Bó et al, 2002, Sá Filho et al, 2010band Sales et al, 2012. Common among these protocols is the insertion of an intravaginal P4 device or a progestin ear implant, plus the administration of an E2 ester on Day 0 [estradiol benzoate (EB) or estradiol valerate to induce the emergence of a new follicular wave], prostaglandin (PG) F 2α on the day of device withdrawal (to ensure luteolysis) and an ovulation inducer used at implant removal, 24 h later or concurrent with the TAI to induce synchronized ovulation (Baruselli et al, 2004, Sá Filho et al, 2011aand Sales et al, 2012.The treatment of cattle with equine chorionic gonadotropin (eCG) has been suggested as an effective tool to increase follicular development and pregnancy per AI (P/AI) in suckled beef cows that exhibit a high prevalence of anestrus or a low body condition score (Baruselli et al, 2004, Sá Filho et al, 2010a, Sá Filho et al, 2010cand Sales et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Common among these protocols is the insertion of an intravaginal P4 device or a progestin ear implant, plus the administration of an E2 ester on Day 0 [estradiol benzoate (EB) or estradiol valerate to induce the emergence of a new follicular wave], prostaglandin (PG) F 2α on the day of device withdrawal (to ensure luteolysis) and an ovulation inducer used at implant removal, 24 h later or concurrent with the TAI to induce synchronized ovulation (Baruselli et al, 2004, Sá Filho et al, 2011aand Sales et al, 2012.The treatment of cattle with equine chorionic gonadotropin (eCG) has been suggested as an effective tool to increase follicular development and pregnancy per AI (P/AI) in suckled beef cows that exhibit a high prevalence of anestrus or a low body condition score (Baruselli et al, 2004, Sá Filho et al, 2010a, Sá Filho et al, 2010cand Sales et al, 2011. The efficiency of this hormone is related to its FSHand LH-like activities (Murphy and Martinuk, 1991), which stimulate the continuation of follicular growth in cows with compromised gonadotropin secretion.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the inclusion of eCG treatment in TAI synchronisation protocols was shown to be advantageous only in cows with a low body condition score at the beginning of the protocol (Souza et al, 2009;Sales et al, 2011) or in anoestrus cows (Garcia-Ispierto et al, 2012). Sales et al (2012) found a significant interaction between eCG treatment and bovine BCSs at the onset of the synchronisation protocol. These authors found that cows presenting a lower BCS had greater pregnancy responses after eCG treatment, and no effect of eCG administration was found when cows presented a greater BCS at onset of the synchronisation protocol (Sales et al, 2011).…”
Section: Resultsmentioning
confidence: 97%
“…In particular, TAI programmes have been applied in postpartum anovular beef cows, anticipating the first postpartum insemination and improving reproductive efficiency under tropical conditions (Baruselli et al, 2004;Sales et al, 2012). The use of equine chorionic gonadotropin (eCG) has improved the efficacy of TAI protocols and increased ovulatory responses and pregnancy rates (Cutaia et al, 2003;Sá Filho et al, 2009, 2010cSales et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Penteado et al (2006) administered EC to B. indicus lactating cows on the day of P 4 removal, resulting in 49.4% PR, indicating that it can be used on the day of P 4 removal. Sales et al (2012) synchronized ovulation in B. indicus cows using EB or EC. They concluded that both esters effectively induced a preovulatory LH peak resulting in synchronized ovulation either by applying EC on P 4 removal or EB 24 h after P 4 removal.…”
Section: Introductionmentioning
confidence: 99%